PVDF (Polyvinylidene Fluoride)-based organic-inorganic composite polymer solid electrolyte as well as preparation method and application thereof
By adding hydrazine-based organic small molecules and lithium salts to the PVDF-based organic-inorganic composite solid electrolyte, the component ratio and preparation process are optimized, and the problems of low conductivity, large interface impedance and poor mechanical properties are solved, and efficient lithium ion conduction and mechanical strength are achieved, which is suitable for high-performance applications of lithium electronic batteries.
Patent Information
- Application Number
- CN202411872183.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing PVDF-based organic-inorganic composite solid electrolyte has low conductivity, large interface impedance, poor mechanical properties and low critical current density.
By adding different contents of hydrazine-based organic-inorganic composite solid electrolyte as organic additives, combining lithium salts and active fillers, optimizing the component ratio and preparation process, a high-performance solid electrolyte is formed.
It significantly improves the lithium-ion conductivity of PVDF-based organic-inorganic composite solid electrolyte, reduces the interface impedance, improves mechanical strength and interface stability, and is suitable for high-performance applications of lithium electronic batteries.
Smart Images

Figure CN119674192A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solid electrolytes, and in particular relates to a PVDF-based organic-inorganic composite polymer solid electrolyte and a preparation method and application thereof. Background Art
[0002] Solid electrolytes have been a hot topic in the field of battery technology in recent years. Compared with liquid electrolytes, they have higher safety and stability. At present, solid electrolytes are mainly divided into the following three types: polymer solid electrolytes, sulfide solid electrolytes, and oxide solid electrolytes.
[0003] Polymer solid electrolytes use polymers as a matrix and use lithium salts to achieve ion conduction. This type of electrolyte has good flexibility and processability, so it is suitable for making thin, bendable solid-state batteries. However, the ionic conductivity of polymer solid electrolytes is relatively low, and the performance is easily affected at high temperatures, which limits its application in high-temperature environments. Polyvinylidene fluoride (PVDF) polymer organic-inorganic composite solid electrolytes have the disadvantages of low conductivity, large interfacial impedance, and low critical current density. Polymer electrolytes mainly conduct lithium ions through the movement of chain segments in the non-crystalline region. In order to reduce crystallinity and improve ionic conductivity, commonly used means or strategies include cross-linking, forming block copolymers, adding plasticizers, and introducing inorganic fillers. Among all these attempts, dispersing inorganic fillers in a polymer matrix to synthesize organic / inorganic composite solid electrolytes has attracted particular attention. This is because this composite method can not only effectively improve ionic conductivity, but also improve the mechanical properties and thermal stability of the electrolyte to a certain extent.
[0004] In addition, by adding ionic plastic crystals, reducing the crystallinity of the polymer can also improve its lithium ion conductivity. Chinese patent document CN114204118A discloses a method for preparing a PVDF-based composite solid electrolyte, which uses the plastic crystal compound succinonitrile to reduce the crystallinity of the polymer and improve the ionic conductivity. The composite solid electrolyte product has high ionic conductivity and a wide electrochemical window as well as good mechanical properties and thermal stability. However, the addition of ionic plastic crystals utilizes the "holes" in the lattice of ionic plastic crystals that move as molecules or ions rotate, so that the plastic crystals have a higher lithium ion conductivity, but have the disadvantages of large interface resistance and low mechanical properties. Summary of the invention
[0005] In order to solve the problems of low conductivity, large interface impedance, poor mechanical properties and low critical current density of polyvinylidene fluoride (PVDF) polymer organic-inorganic composite solid electrolyte in the prior art, the present invention provides a preparation and application of a PVDF-based organic-inorganic composite polymer solid electrolyte.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A PVDF-based organic-inorganic composite polymer solid electrolyte comprises PVDF, a lithium salt, an active filler and an organic additive, wherein the mass ratio of PVDF to the lithium salt is (1-20):1, the mass ratio of the total mass of PVDF and the lithium salt to the active filler is (3-30):1, the mass ratio of the total mass of PVDF and the lithium salt to the organic additive is (2-20):1, and the organic additive is a hydrazine compound.
[0008] Preferably, the mass ratio of the total mass of PVDF and lithium salt to the active filler is (3-14):1, and the mass ratio of the total mass of PVDF and lithium salt to the organic additive is (2-5):1. More preferably, the mass ratio of PVDF to lithium salt is 3:1, the mass ratio of the total mass of PVDF and lithium salt to the active filler is 4:1, and the mass ratio of the total mass of PVDF and lithium salt to the organic additive is 3:1.
[0009] Preferably, the lithium salt includes one or more of LiFSI, LiTFSI, LiBOB, LiODFB, LiBF4, LiPO2F2, and LiAsF6. More preferably, LiPO2F2.
[0010] Preferably, the active filler includes one or more of lithium lanthanum zirconium tantalum oxide (LLZTO), lithium indium chloride (Li3InCl6), lithium yttrium chloride (Li3YCl6), lithium zirconium chloride (Li2ZrCl6), lithium tantalum chloride (LiTaCl6), lithium aluminum titanium phosphide (LATP), lithium aluminum germanium phosphide (LGTP) and lithium phosphorus sulfur chloride (LPSCl). More preferably, Li2ZrCl6 and LATP are used, and more preferably, LATP is used.
[0011] Preferably, the organic additives include 3,5-dimethylphenylhydrazine hydrochloride, 2-nitrobenzylhydrazine, diphenylcarbazide, 3-cyanophenylhydrazine hydrochloride, N,N'-diacetylhydrazine, stearylhydrazine, 4-aminobenzoylhydrazine, pyrazine-2-hydrazine, 3,5-bis(trifluoromethyl)phenylhydrazine hydrochloride, 3-fluorobenzoylhydrazine, 3-(trifluoromethyl)phenylhydrazine hydrochloride, dimethylhydrazine pyridine, 1,1-dimethylhydrazine hydrochloride, crotonaldehyde 2,4-dinitro Phenylhydrazine, thiocarbohydrazine, 2-furancarboxylic acid hydrazide, 2,2-biphenyl-1-picrylhydrazyl, 4-trifluoromethylphenylhydrazine hydrochloride, azidine, (α,α,α,2,3,5,6-heptafluoro-o-tolyl) hydrazine, p-tolylhydrazine, oxalic acid bis(benzylidenehydrazine), 4-cyanophenylhydrazine hydrochloride, nicotinic acid hydrazide, maleic acid dihydrazide, 2-hydrazine alcohol, 3,4-dimethoxyphenylhydrazine hydrochloride, 2,3,5,6-tetrafluorophenylhydrazine, 2-naphthoic acid hydrazide. Further preferably, the organic additive is crotonaldehyde 2,4-dinitrophenylhydrazine, (α,α,α,2,3,5,6-heptafluoro-o-tolyl) hydrazine, and further preferably (α,α,α,2,3,5,6-heptafluoro-o-tolyl) hydrazine.
[0012] The present invention also provides a method for preparing the above-mentioned solid electrolyte, comprising weighing PVDF and LiTFSI according to a mass ratio, adding LLZTO powder and 3,5-dimethylphenylhydrazine hydrochloride, adding a solvent, heating and stirring to obtain a uniformly mixed slurry, casting the slurry into a film, and vacuum drying to obtain the solid electrolyte.
[0013] Preferably, the solid content of the slurry is 20-40%.
[0014] Preferably, the organic solvent includes one or more of acetonitrile, dimethylacetamide (DMAC), dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), N,N-dimethylformamide and the like.
[0015] Preferably, the heating temperature is 20-150°C, preferably 35-85°C.
[0016] Preferably, the stirring time is 8 to 60 hours, preferably 8 to 30 hours.
[0017] Preferably, the temperature used for vacuum drying is 20 to 100° C., preferably 40 to 90° C.; the time used for vacuum drying is 2 to 48 hours, preferably 8 to 30 hours.
[0018] The present invention also provides an application of a PVDF-based organic-inorganic composite polymer solid electrolyte in the preparation of a lithium electronic battery.
[0019] Beneficial effects of the present invention:
[0020] (1) The present invention improves the performance of the battery by adding different amounts of organic small molecule additives to a polyvinylidene fluoride (PVDF)-based organic-inorganic composite solid electrolyte. Hydrazine-based organic small molecule compounds have strong electron-donating properties and extremely strong reducibility. The extremely strong electron-donating properties can improve the dissociation of lithium salts, thereby improving the lithium ion conductivity of the solid electrolyte. The extremely strong reducibility can induce the uniform deposition of lithium ions and form a stable interface layer rich in Li3N-LiF on the interface, effectively improving the interface stability.
[0021] (2) The introduction of organic small molecule additives in the present invention can effectively improve the ionic conductivity of PVDF-based organic-inorganic composite solid electrolytes at near room temperature (up to 1.3×10 -3 S cm -1 ). After the introduction of organic small molecules, a high-performance interface layer is formed in situ with lithium salt, which significantly improves the interfacial compatibility between the organic-inorganic composite solid electrolyte and lithium metal, and the interfacial impedance is as low as below 20Ω. By introducing lithium salt additives and organic small molecules, the mechanical strength of the organic-inorganic composite solid electrolyte is improved to more than 6.5MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a test graph of lithium ion conductivity of the PVDF-based organic-inorganic composite polymer electrolyte membrane obtained in Example 1;
[0023] Figure 2 This is a graph showing the interfacial impedance of the PVDF-based organic-inorganic composite polymer electrolyte membrane obtained in Example 1;
[0024] Figure 3 This is a test graph of lithium ion conductivity of the PVDF-based organic-inorganic composite polymer electrolyte membrane obtained in Example 2;
[0025] Figure 4 This is a graph showing the interfacial impedance of the PVDF-based organic-inorganic composite polymer electrolyte membrane obtained in Example 2;
[0026] Figure 5 This is a test graph of lithium ion conductivity of the PVDF-based organic-inorganic composite polymer electrolyte membrane obtained in Example 3;
[0027] Figure 6 This is a graph showing the interfacial impedance of the PVDF-based organic-inorganic composite polymer electrolyte membrane obtained in Example 3;
[0028] Figure 7 This is a test graph of lithium ion conductivity of the PVDF-based organic-inorganic composite polymer electrolyte membrane obtained in Example 4;
[0029] Figure 8This is a graph showing the interfacial impedance of the PVDF-based organic-inorganic composite polymer electrolyte membrane obtained in Example 4;
[0030] Fig. 9 This is a test graph of lithium ion conductivity of the PVDF-based organic-inorganic composite polymer electrolyte membrane obtained in Example 5;
[0031] Fig.10 This is a graph showing the interfacial impedance of the PVDF-based organic-inorganic composite polymer electrolyte membrane obtained in Example 5;
[0032] Fig.11 This is a test graph of lithium ion conductivity of the PVDF-based organic-inorganic composite polymer electrolyte membrane obtained in Example 6;
[0033] Fig.12 This is a graph showing the interfacial impedance of the PVDF-based organic-inorganic composite polymer electrolyte membrane obtained in Example 6;
[0034] Fig.13 This is a test graph of lithium ion conductivity of the PVDF-based organic-inorganic composite polymer electrolyte membrane obtained in Example 7;
[0035] Fig.14 This is a graph showing the interfacial impedance of the PVDF-based organic-inorganic composite polymer electrolyte membrane obtained in Example 7;
[0036] Fig.15 This is a test graph of lithium ion conductivity of the PVDF-based organic-inorganic composite polymer electrolyte membrane obtained in Example 8;
[0037] Fig.16 This is a graph showing the interfacial impedance of the PVDF-based organic-inorganic composite polymer electrolyte membrane obtained in Example 8;
[0038] Fig.17 The lithium ion conductivity test diagram of the PVDF-based organic-inorganic composite polymer electrolyte membrane obtained in Example 1;
[0039] Fig.18 This is a graph showing the interfacial impedance of the PVDF-based organic-inorganic composite polymer electrolyte membrane obtained in Example 1. DETAILED DESCRIPTION
[0040] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0041] In the following examples, unless otherwise specified, all reagents used are commercially available reagents, and the PVDF used is Arkema PVDF761.
[0042] The detection means and methods used are conventional detection means and methods in this field, among which the ionic conductivity and interface impedance are tested at room temperature (25°C) using an electrochemical workstation. The full battery performance is tested at room temperature (25°C) using a solid-state battery with lithium iron phosphate as the positive electrode. The mechanical strength is tested at room temperature (25°C) using a nanoindenter.
[0043] Example 1
[0044] 3 g PVDF and 1 g LiTFSI were weighed according to the mass ratio of PVDF:LiTFSI = 3:1, and then 0.133 g LLZTO (Li 6.5 LqCy 1.5 Ta 0.5 O 12 ) powder and 0.2g 3,5-dimethylphenylhydrazine hydrochloride. DMSO was added as a solvent, and the mixture was heated and stirred at 35°C for 15h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 55°C for 20h to obtain a PVDF-based organic-inorganic composite polymer electrolyte membrane. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 1.7×10 -4 S / cm( Figure 1 ), and its interface impedance is 100.5Ω( Figure 2 ), the critical current density is 0.4 mA / cm 2 , and its elastic simulation can reach 4.5MPa. After 100 cycles at 0.5C, the capacity retention rate reaches 81%.
[0045] Example 2
[0046] 5g PVDF and 0.25g LiBOB were weighed according to the mass ratio of PVDF:LiBOB = 20:1, and then 1.75g Li3YCl6 powder and 0.525g thiocarbazide were added. NMP was added as a solvent, and the mixture was heated and stirred at 55°C for 25h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 45°C for 24h to obtain a PVDF-based organic-inorganic composite polymer electrolyte membrane. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 2.9×10 -4 S / cm( Figure 3 ), and its interface impedance is 90.7Ω( Figure 4 ), the critical current density is 0.7 mA / cm 2 , and its elastic simulation can reach 5.2MPa. After 100 cycles at 0.5C, the capacity retention rate reaches 86%.
[0047] Example 3
[0048] 2g PVDF and 2g LiBF4 were weighed according to the mass ratio of PVDF:LiBF4 = 1:1, and then 0.4g Li3YCl6 powder and 2g stearic hydrazide were added. NMP was added as a solvent, and the mixture was heated and stirred at 85°C for 8h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 85°C for 12h to obtain a PVDF-based organic-inorganic composite polymer electrolyte membrane. After cutting, its lithium ion conductivity was tested and its lithium ion conductivity was 5.1×10 -4 S / cm( Figure 5 ), and its interface impedance is 121.7Ω( Figure 6 ), the critical current density is 0.9 mA / cm 2 , and its elastic simulation can reach 5.9MPa. After 200 cycles at 0.5C, the capacity retention rate is 81.2%.
[0049] Example 4
[0050] 10g PVDF and 0.5g LiPO2F2 were weighed according to the mass ratio of PVDF:LiPO2F2 = 20:1, and then 0.75g Li2ZrCl6 powder and 2.1g crotonaldehyde 2,4-dinitrophenylhydrazine were added. DMAC was added as a solvent, and the mixture was heated and stirred at 75°C for 30h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 90°C for 8h to obtain a PVDF-based organic-inorganic composite polymer electrolyte membrane. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 6.7×10 -4 S / cm( Figure 7 ), and its interface impedance is 32.4Ω( Figure 8 ), the critical current density is 1.2 mA / cm 2 , and its elastic simulation can reach 6.5MPa. After 150 cycles at 0.5C, the capacity retention rate reaches 89%.
[0051] Example 5
[0052] Weigh 3g PVDF and 1g LiPO2F2 at a mass ratio of PVDF:LiAsF6 = 3:1, then add 1g LATP (Li 1.3 Al 0.3 Ti 1.7 (PO4)3,) powder and 1.33g (α,α,α,2,3,5,6-heptafluoro-o-tolyl) hydrazine. DMAC was added as a solvent, heated and stirred at 65°C for 24h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 40°C for 16h to obtain a PVDF-based organic-inorganic composite polymer electrolyte membrane. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 1.3×10-3 S / cm( Fig. 9 ), and its interface impedance is 14.3Ω( Fig.10 ), the critical current density is 1.5 mA / cm 2 , and its elastic simulation can reach 7.7MPa. After 200 cycles at 0.5C, the capacity retention rate reaches 92%.
[0053] Example 6
[0054] 3g PVDF and 1g LiPO2F2 were weighed according to the mass ratio of PVDF:LiAsF6=3:1, and then 1g LATP powder and 2g (α,α,α,2,3,5,6-heptafluoro-o-tolyl) hydrazine were added. DMAC was added as a solvent, and the mixture was heated and stirred at 65°C for 24h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 40°C for 16h to obtain a PVDF-based organic-inorganic composite polymer electrolyte membrane. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 8.6×10 -4 S / cm( Fig.11 ), and its interface impedance is 31.5Ω( Fig.12 ), the critical current density is 1.1 mA / cm 2 , and its elastic simulation can reach 7.2MPa. After 200 cycles at 0.5C, the capacity retention rate reaches 85%.
[0055] Example 7
[0056] 3g PVDF and 1g LiPO2F2 were weighed according to the mass ratio of PVDF:LiAsF6=3:1, and then 1.33g LATP powder and 1.33g (α,α,α,2,3,5,6-heptafluoro-o-tolyl) hydrazine were added. DMAC was added as a solvent, and the mixture was heated and stirred at 65°C for 24h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 40°C for 16h to obtain a PVDF-based organic-inorganic composite polymer electrolyte membrane. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 7.1×10 -4 S / cm( Fig.13 ), and its interface impedance is 34.3Ω( Fig.14 ), the critical current density is 0.8 mA / cm 2 , and its elastic simulation can reach 6.5MPa. Its solid-state battery with lithium iron phosphate as the positive electrode can be cycled 200 times at 0.5C at room temperature, and the capacity retention rate reaches 80.7%.
[0057] Example 8
[0058] 3g PVDF and 1g LiPO2F2 were weighed according to the mass ratio of PVDF:LiAsF6=3:1, and then 1g LATP powder and 1.33g 4-trifluoromethylphenylhydrazine hydrochloride were added. DMAC was added as a solvent, and the mixture was heated and stirred at 65°C for 24h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 40°C for 16h to obtain a PVDF-based organic-inorganic composite polymer electrolyte membrane. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 6.4×10 -4 S / cm( Fig.15 ), and its interface impedance is 52.7Ω( Fig.16 ), the critical current density is 0.5 mA / cm 2 , and its elastic simulation can reach 5.5MPa. Its solid-state battery with lithium iron phosphate as the positive electrode can be cycled 200 times at 0.5C at room temperature, and the capacity retention rate reaches 72%.
[0059] Comparative Example 1
[0060] 3g PVDF and 1g LiPO2F2 were weighed according to the mass ratio of PVDF:LiAsF6=3:1, and then 1g LATP powder was added. DMAC was added as a solvent, and the mixture was heated and stirred at 65°C for 24h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 40°C for 16h to obtain a PVDF-based organic-inorganic composite polymer electrolyte membrane. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 9.1×10 -5 S / cm( Fig.17 ), and its interface impedance is 237.5Ω( Fig.18 ), the critical current density is 0.2 mA / cm 2 , and its elastic simulation can reach 1.2MPa. Its solid-state battery with lithium iron phosphate as the positive electrode can maintain a capacity of 65% after 100 cycles at 0.5C at room temperature.
Claims
1. A PVDF-based organic-inorganic composite polymer solid electrolyte, characterized in that: The invention comprises PVDF, lithium salt, active filler and organic additive, wherein the mass ratio of PVDF to lithium salt is (1-20):1, the mass ratio of the total mass of PVDF and lithium salt to the active filler is (3-30):1, the mass ratio of the total mass of PVDF and lithium salt to the organic additive is (2-20):1, and the organic additive is a hydrazine compound.
2. The solid electrolyte according to claim 1, characterized in that The mass ratio of the total mass of PVDF and lithium salt to the active filler is (3-14):1, and the mass ratio of the total mass of PVDF and lithium salt to the organic additive is (2-5):
1.
3. The solid electrolyte according to claim 1, characterized in that The lithium salt includes one or more of LiFSI, LiTFSI, LiBOB, LiODFB, LiBF4, LiPO2F2, and LiAsF6, preferably LiPO2F2.
4. The solid electrolyte according to claim 1, characterized in that The active filler includes one or more of lithium lanthanum zirconium tantalum oxide, lithium indium chloride, lithium yttrium chloride, lithium zirconium chloride, lithium tantalum chloride, lithium aluminum titanium phosphide, lithium aluminum germanium phosphide or lithium phosphorus sulfur chlorine, preferably Li2ZrCl6 or LATP.
5. The solid electrolyte according to claim 1, characterized in that The organic additives include 3,5-dimethylphenylhydrazine hydrochloride, 2-nitrobenzylhydrazine, diphenylcarbazide, 3-cyanophenylhydrazine hydrochloride, N,N'-diacetylhydrazine, stearylhydrazine, 4-aminobenzoylhydrazine, pyrazine-2-hydrazine, 3,5-bis(trifluoromethyl)phenylhydrazine hydrochloride, 3-fluorobenzoylhydrazine, 3-(trifluoromethyl)phenylhydrazine hydrochloride, dimethylhydrazine pyridine, 1,1-dimethylhydrazine hydrochloride, crotonaldehyde 2,4-dinitrophenylhydrazine , thiocarbohydrazide, 2-furocarboxylic acid hydrazide, 2,2-biphenyl-1-picrylhydrazyl, 4-trifluoromethylphenylhydrazine hydrochloride, azidine, (α,α,α,2,3,5,6-heptafluoro-o-tolyl)hydrazine, p-tolylhydrazine, oxalic acid bis(benzylidenehydrazine), 4-cyanophenylhydrazine hydrochloride, nicotinic acid hydrazide, maleic acid dihydrazide, 2-hydrazine alcohol, 3,4-dimethoxyphenylhydrazine hydrochloride, 2,3,5,6-tetrafluorophenylhydrazine, 2-naphthoic acid hydrazide. Preferably, the organic additive is crotonaldehyde 2,4-dinitrophenylhydrazine, (α,α,α,2,3,5,6-heptafluoro-o-tolyl)hydrazine.
6. The method for preparing the solid electrolyte according to any one of claims 1 to 5, characterized in that: PVDF and LiTFSI are weighed respectively according to the mass ratio, and then LLZTO powder and 3,5-dimethylphenylhydrazine hydrochloride are added, and a solvent is added, and a uniformly mixed slurry is obtained by stirring under heating. The slurry is cast into a film, and the film is obtained after vacuum drying.
7. The preparation method according to claim 6, characterized in that: The organic solvent includes one or more of acetonitrile, dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidine, and N,N-dimethylformamide.
8. The preparation method according to claim 6, characterized in that: The heating temperature is 20-150° C., and the stirring time is 8-60 hours; the temperature used for vacuum drying is 20-100° C., and the time is 2-48 hours.
9. The preparation method according to claim 8, characterized in that: The heating temperature is 35-85° C., and the stirring time is 8-30 hours; the temperature used for vacuum drying is 40-90° C., and the time is 8-30 hours.
10. Use of the PVDF-based organic-inorganic composite polymer solid electrolyte according to any one of claims 1 to 5 or the PVDF-based organic-inorganic composite polymer solid electrolyte prepared by the method according to any one of claims 6 to 9 in preparing lithium electronic batteries.
Citation Information
Patent Citations
PVDF-based composite solid electrolyte and preparation method thereof
CN114204118A
Composite solid electrolyte and preparation method and application thereof
CN113471523A
Ion conductive solid electrolyte
JP2006032000A